FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN PENYELESAIAN STUDI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FT-UNP - 492-501 , Elfredo Dwipa Regia (Universitas Negeri Padang, 2015)
Abstract This research is a qualitative descriptive research that aims to reveal the factors that influence the delay in the completion of studies students of Education Building Engineering Department of Civil Engineering FT-UNP. Allegedly there are two main factors causing delays in the student studies, which delays the completion of the course and delay the completion of the essay. Both of these factors then sought the cause in terms of both internal and external. The population in this study are students who have passed through the study of 8 semesters that of 2007, 2008 and 2009 were still active in the semester from January to June 2014. Samples were taken using the technique of